Pentingnya Pendidikan Islam Dalam Membentuk Karakter Generasi Muda - Astuti, Mardiah; Herlina, Herlina; Ibrahim, Ibrahim; Juliansyah, Juliansyah; Febriani, Reni; Oktarina, Nining (STAI Denpasar Bali, 2023)
This article discusses the importance of Islamic education in building the character of the younger generation. Nowadays, many young people are entangled in things that are not in accordance with good character. The goal is to teach universal values that can be embraced by all levels of society. Thus, Islamic education not only plays an important role in shaping the character of the younger generation, but also contributes to the development of society and the nation. This research uses Qualitative Method, to obtain data through literature study, about the process of character building for the younger generation. Islamic education can help the younger generation to understand moral and spiritual values that are very important for human life. In addition, Islamic education can also help the younger generation to overcome social problems and avoid negative behavior. Islamic education provides the moral, ethical and spiritual foundation needed to face the challenges of the modern world and build a generation of young people of good character who care for others and make a positive contribution to society.